The Theory of Understanding in Francisco de Encina (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
In this article, I intend to prove that at the foundation of Francisco Antonio Encina’s thought there is a reflection on human understanding. This reflection, unlike what some authors have argued, has a philosophical scope. In it are exposed, in a relevant manner: the poles between which understanding is made; the extremes toward which comprehensive activity can lean; and the basic conditions that must be met by an understanding of human affairs that can be qualified as pertinent, adequate or correct.
Keywords: Hermeneutics; political understanding; historical understanding; realism